Some economic effects of changing augmentation rules in Colorado's lower South Platte Basin: producer survey and regional economic impact analysis - Thorvaldson, Jennifer, author; Pritchett, James, author; Colorado Water Resources Research Institute, publisher (Colorado State University. Libraries, 2007)
The purposes of this study are three-fold: first, to describe the economic benefits of affirming the property rights which occurred as a result of the change in augmentation rules; second, to examine how affected farmers responded to the change in augmentation rules; and third, to quantify some of the economic impacts to the LSP as a result of the augmentation rule changes. As water continues to be transferred from agricultural to M&I2, recreational, and environmental uses, and with drought remaining a constant threat, further reductions in irrigated agriculture are sure to occur in the future. By estimating the size and scope of the economic impact of such acreage reductions, it is hoped that this study will help affected communities mitigate, prepare for, and adjust to such impacts.
July 2007.
Keywords: Irrigation -- Economic aspects -- Colorado; Agriculture -- Economic aspects -- Colorado; Water rights -- Colorado